2021
DOI: 10.1021/acs.jctc.1c00936
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic Generalized Active Space Self-Consistent Field: Theory and Application

Abstract: An algorithm to perform stochastic generalized active space calculations, Stochastic-GAS, is presented, that uses the Slater determinant based FCIQMC algorithm as configuration interaction eigensolver. Stochastic-GAS allows the construction and stochastic optimization of preselected truncated configuration interaction wave functions, either to reduce the computational costs of large active space wave function optimizations, or to probe the role of specific electron correlation pathways. As for the conventional… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
85
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(97 citation statements)
references
References 108 publications
(302 reference statements)
7
85
0
Order By: Relevance
“… 48 In a recent study, Stochastic-MRCISD calculations have shown further evidence of a correlation-induced differential stabilization of the 3 E g state over the 5 A 1g . 49 In this work, we focus on the quintet–triplet spin gap Δ E = E Q – E T , which is estimated to be in a range of a few kcal/mol.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… 48 In a recent study, Stochastic-MRCISD calculations have shown further evidence of a correlation-induced differential stabilization of the 3 E g state over the 5 A 1g . 49 In this work, we focus on the quintet–triplet spin gap Δ E = E Q – E T , which is estimated to be in a range of a few kcal/mol.…”
Section: Resultsmentioning
confidence: 99%
“…These orbitals have also been used in other works of ours and are described there in greater detail. 48 , 49 , 104 , 105 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The electronic structural description of iron porphyrins is also of fundamental interest, as these systems are prototypical of large, strongly correlated systems where determining the spin-state ordering is still challenging. For even the simplest, unfunctionalized iron­(II) porphyrin (FeP), the ordering of the lowest lying spin states is still being studied with recently developed, sophisticated electronic structure methods. …”
Section: Introductionmentioning
confidence: 99%
“…This has proven a successful means of sampling one-and two-body RDMs in fermionic systems for a diversity of applications, e.g. molecular properties [112,113], MCSCF orbital optimisations [59,[114][115][116] and contributions from internally contracted perturbers in multireference perturbation theories [117,118]. However, this approach makes an approximation that the set of configurational pairs, (i, j) with non-zero coefficient product which contribute to the RDMs of interest (Γ-connections) is equal to the set of (i, j) pairs connected by a non-zero Hamiltonian matrix element (H-connections).…”
Section: A Reduced Density Matrix Samplingmentioning
confidence: 99%